MiR-3099 is overexpressed in differentiating 46c mouse embryonic stem cells upon neural induction - Zainal Abidin, Shahidee; Abbaspourbabaei, Maryam; Ntimi, Carolindah Makena; Siew, Wei Hong; Cheah , Pike See; Rosli, Rozita; Nordin, Norshariza; Ling, King Hwa (Penerbit Universiti Sains Malaysia, 2014)
Background: MicroRNAs (miRNAs) have a crucial role in gene expression regulation and protein synthesis, especially in the central nervous system. In developing mouse embryos a novel miRNA, miR-3099, is highly expressed, particularly in the central nervous system. This study aims to determine the expression of miR-3099 during cellular differentiation of 46C mouse embryonic stem cells after neural induction with N2/B27 medium.